A New Robust Decoupled Control of the Stator Active and Reactive Currents for Grid-Connected Doubly-Fed Induction Generators - Ahmad Bashar Ataji; Yushi Miura; Toshifumi Ise; Hiroki Tanaka (Energies, 2016)
This paper addresses the grid-connected variable speed doubly-fed induction generator, and proposes a new decoupled control to replace the conventional decoupled active and reactive powers (P-Q) control. The proposed decoupled control is based on decoupling the stator active and reactive currents, in contrast with the conventional decoupled P-Q control, which is based on decoupling the stator active and reactive powers by forcing the stator d- or q-voltage to zero. The proposed decoupled control has all the advantages of the conventional decoupled P-Q control such as constant switching frequency and robustness against slip angle inaccuracy, and it has some additional advantages: The proposed control requires less machine parameters; for the controller design, it requires the stator-to-rotor turns ratio only; for the online calculation, it does not requires any machine parameter. The proposed decoupled control is more flexible and robust since the control is independent of the grid voltage orientation. It is robust against variation in the grid voltage amplitude. Several experiments are carried out using a 1.1 kW doubly-fed induction generator (DFIG), and the results support the proposed decoupled control and demonstrate some of its advantages.